Kinerja Mengajar dengan Sistem Work From Home (WFH) pada Guru di SMK Purnawarman Purwakarta - Busyra, Sarah; Sani, Lutfiah (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2020)
This article tries to identify the teaching performance of teachers at SMK PurnawarmanPurwakarta using the Work From Home (WFH) system during the Covid-19 pandemic. Thepopulation of this study is teachers at SMK Purnawarman Purwakarta which is 22 teachers. Themethod used mixture of Explanation Sequential, which is qualitative data can explain furthermore or strengthen the initial quantitative data. The results ot this study used descriptivestatistical analysis with quantitative descriptive forms that are collaborated with descriptivequalitative data analysis. Data collection techniques using questionnaires, interviews anddocumentation in the form of school data. The results of this study showed the averageperformance of teachers in teaching using work from home system is only 50%. Overall, theperformance results do not exceed the 70% limit. It happened because several factors are thehalf of the teachers do not understand some applications that used in teaching, also the distancescaused the teachers face obstacles in interaction with students optimally.